Pengaruh Opini Audit, dan Audit Delay Terhadap Kualitas Laporan Keuangan Dengan Profitabilitas Sebagai Variabel Moderasi (Pada Bank Umum Syariah di Indonesia Periode 2018 – 2022) - Samsiah Samsiah; Aisyah Ratnasari; Hani Hasanah; Kristanti Kristanti (Jurnal Manajemen Riset Inovasi, 2024)
The purpose of this study was to identify and analyze the impact of audit opinion and audit delay partially on the quality of financial statements, with profitability variables as moderating. This research was conducted at Islamic commercial banks registered with the financial services authority during the period 2018-2022. This type of research uses a quantitative approach, the research population involves a total of 11 Islamic commercial banks. The sample in the study was selected using purposive sampling method, which resulted in 11 samples with observations for 5 years. Hypothesis testing in this study used a panel data regression model with the Fixed Effect Model (FEM) approach and for testing the moderation variable using the MRA (Moderated Regression Analysis) model. The results of this study indicate that the partial results of audit opinion have a positive and significant effect on the quality of financial statements, while audit delay has a negative and significant effect on the quality of financial statements, while profitability is unable to moderate the effect of audit opinion on the quality of financial statements. Meanwhile, profitability is not able to moderate the effect of audit delay on the quality of financial statements.